AN ANALYSIS OF THE EARLY DISCOURSE OF BALINESE PRESCHOOL CHILDREN’S DIRECT SPEECH IN SINGARAJA - Meiyana Ariss Susanti, I Luh (International Journal of Language and Literature, 2019)
This study analyzes the early language development of young Balinese preschool children in Singaraja. Specifically, the study focuses on the early discourse abilities of the novice language learners. The study involved ten 4 – years – old preschool children and their caregivers (parents, extended family members, and nannies) from Singaraja. The data were analyzed to see what discourse types were used by the children and in what language (Indonesian or Balinese). The results suggest that children produce more response discourse type in their utterances due to the fact that these young language learners have very limited communicative repertoire. It seems that their conversation range primarily revolves around the typical question and answer conversational dyad. Furthermore, it has been found that young children make use of the Indonesian language in their responses more than their native language (Balinese language). This language preference may be due to the fact that children are exposed to L2 influences such as: movies, song, and other learning materials.